Speechless. The complete second season [videorecording (DVD)] - Driver, Minnie; Bowie, John Ross, 1971-; Cook, Mason, 2000- (20th Century Fox, 2018)
Maya DiMeo is the mom who will do anything for her husband Jimmy and kids Ray, Dylan, and J.J., her eldest son with cerebral palsy. In season two of this amusing and often unexpected comedy, the family, along with JJ's aide Kenneth, is reunited after JJ's first summer camp adventure. As the new school year approaches, the DiMeos, who have been searching endlessly for the right school support for JJ, are faced with a new and unfamiliar reality: the kids are going to continue at the same school! It's uncharted territory but, as always, the DiMeos will find a fun balance in everything they do.